P106 Robotic Roux-en-Y gastric bypass: A systematic review to examine reporting of a surgical innovation. (8th April 2021) - Robertson, H; Huttman, M; Dixon, L; Macefield, R; Hossaini, S; Scroggie, D; ,; Robertson, Harry
Abstract: Introduction: Roux-en-Y gastric bypass (RYGB) is one of the most commonly performed bariatric procedures, and robotic methods are increasingly used. Perceived benefits of robotic surgery include improved visualisation and ergonomics, fewer complications, and shorter hospital stay. Rigorous processes that facilitate the safe transition of surgical innovations such as robotic RYGB into clinical practice are currently lacking. This may place patients at risk, and lead to research waste. The IDEAL Collaboration has produced guidance on the reporting of surgical innovations, but it is not known how robotic RYGB has been reported. This project aims to summarise technique description, governance arrangements and outcome reporting in robotic RYGB. Methods: A systematic review is being conducted, using PRISMA guidance. A search of Embase, Ovid Medline, the Cochrane Library and Web of Science was performed to identify primary studies reporting outcomes of robotic RYGB. Data will be extracted on study characteristics, governance and ethical arrangements, descriptions of technique, and outcomes. The data will be evaluated in relation to IDEAL principles. Results: The literature search yielded 1012 studies; 754 remained after de-duplication. Following screening by abstract, 229 full texts were screened. 67 studies will undergo extraction of data. A descriptive summary of the data will be presented, with a critique of the findings. Conclusion: This study will summarise and appraise how robotic RYGB has been reported. This will contribute towards the development of a standardised and methodical process for the introduction of surgical innovation into clinical practice.